Engineered Bacteria EcN-MT Alleviate Liver Injury in Cadmium-Exposed Mice via its Probiotics Characteristics and Expressing of Metallothionein - Zou, Changwei; Chen, Ying; Li, Hongyu; Li, Wenyu; Wei, Jin; Li, Ziyan; Wang, Xinliang; Chen, Tingtao; Huang, Hong (Frontiers in Pharmacology, 2022)
Cadmium (Cd) exposure is a widespread problem in many parts of the world, but effective means to treat Cd exposure is still lacking. Hence, an engineered strain expressing metallothionein (MT) named Escherichia coli Nissle1917 (EcN)-MT was constructed, and its potential in the treatment of Cd exposure was evaluated. The in vitro studies showed that metallothionein expressed by EcN-MT could significantly bind cadmium. Further, the in vivo results indicated that EcN-MT strain could reduce 26.3% Cd in the liver and increase 24.7% Cd in the feces, which greatly decreased malondialdehyde (MDA) levels and increased catalase (CAT), glutathione (GSH), and superoxide dismutase (SOD) levels in liver, and reduced the expression of toll-like receptor4 (TLR4), nuclear factor-κB (NF-κB), the myeloid differentiation factor 88 (Myd88) and increased B-cell lymphoma 2 (Bcl-2)/ Bcl-2-Associated X (Bax). Moreover, high throughput sequencing results indicated that EcN-MT strain greatly enhanced the beneficial bacteria of Ruminococcaceae, Lactobacillaceae, Akkermansia, Muribaculaceae, Lachnospiraceae, Dubosiella and restored the disturbed microbial ecology to the normal level. Therefore, the high Cd binding capacity of the expressed metallothionein, together with the beneficial characteristics of the host bacteria EcN, makes EcN-MT a sound reagent for the treatment of subchronic cadmium exposure-induced liver injury.